A Quantum Lightning Search Algorithm-Based Fuzzy Speed Controller for Induction Motor Drive - Hannan M.A.; Ali J.A.; Hussain A.; Hasim F.H.; Amirulddin U.A.U.; Uddin M.N.; Blaabjerg F. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric drives; Electric inverters; Fuzzy logic; Induction motors; Learning algorithms; Lightning; MATLAB; Membership functions; Optimization; Pulse width modulation; Speed; Speed control; Statistics; Switches; Vector spaces; Voltage control; IM drive; Search Algorithms; Sociology; Space vector pulse width modulation; Speed controller; SVPWM; validation; Controllers